COMPLIANCE OF PREGNANT WOMEN IN TAKING IRON SUPPLEMENTS AND THE INCIDENCE OF ANEMIA IN THE THIRD TRIMESTER : A CROSS SECTIONAL STUDY - Siska Delvia (LPPM STIKES Al-Ma'arif Baturaja, 2026)
Anemia in third-trimester pregnant women remains a significant health problem that can increase the risk of maternal and fetal complications. One of the efforts to prevent anemia is adherence to iron (Fe) tablet consumption as recommended. This study aimed to determine the relationship between adherence to Fe tablet consumption and the incidence of anemia in third-trimester pregnant women at TPMB Bdn. Titik Aryanti, S.Keb. This study employed an analytical design with a cross-sectional approach. The population and sample consisted of all third-trimester pregnant women who attended antenatal care at TPMB Bdn. Titik Aryanti, S.Keb, with a total of 37 respondents selected using total sampling technique. Data on adherence to Fe tablet consumption were collected using a questionnaire, while anemia status was determined based on hemoglobin examination results. Data analysis was conducted using an appropriate statistical test. The results showed a statistically significant relationship between adherence to Fe tablet consumption and the incidence of anemia in third-trimester pregnant women, with a p-value of 0.034 (p < 0.05). In conclusion, there is a significant association between adherence to Fe tablet consumption and the incidence of anemia in third-trimester pregnant women. Health care providers are expected to enhance education and monitoring of Fe tablet consumption adherence to prevent anemia during pregnancy